2004
DOI: 10.1093/humupd/dmh013
|View full text |Cite
|
Sign up to set email alerts
|

Medically assisted reproduction in the presence of chronic viral diseases

Abstract: Teams practising medically assisted reproduction techniques try to avoid viruses as much as possible. Attitudes towards chronic carriers of viruses are rapidly changing, especially for human immunodeficiency virus (HIV) patients. We focus our attention on the legitimacy of systematic screening before assisted reproductive techniques and the need for specialized approaches including an adapted laboratory for viral hazards as well as the need for a multidisciplinary team. Specificities of HIV, hepatitis C virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 151 publications
2
59
0
4
Order By: Relevance
“…The integration between HBV DNA and the sperm chromosome was random and at multiple loci, which further increases the instability of the chromosomes, indicating that HBV infection may have a widespread impact by altering the genetic composition generation after generation. In 2004, Englert et al (17) reported that with assisted reproductive technology (ART), washed gradient centrifugation can be used to reduce the HBV load and avoid transmission to embryos. The sperm underwent washing and ART, and subsequently the spread of HBV was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The integration between HBV DNA and the sperm chromosome was random and at multiple loci, which further increases the instability of the chromosomes, indicating that HBV infection may have a widespread impact by altering the genetic composition generation after generation. In 2004, Englert et al (17) reported that with assisted reproductive technology (ART), washed gradient centrifugation can be used to reduce the HBV load and avoid transmission to embryos. The sperm underwent washing and ART, and subsequently the spread of HBV was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…centrifugation on a density gradient followed by a "swim-up" (reviewed by Englert et al, 2004). Spermatozoa from virally infected men prepared by this method have been used in assisted reproduction attempts, apparently without sero-conversion of mothers or children.…”
Section: Removal Of Viruses From Ejaculatesmentioning
confidence: 99%
“…However, concerns regarding the treatment of patients with potential seminal pathogens during ART include: i) the probability of vertical and horizontal transmission of the specific pathogen, ii) the welfare of children with infected parents that may pass away due to the infection (Lyerly and Anderson, 2001) and iii) the possibility of nosocomial transfer of pathogens in an ART laboratory (Englert et al, 2004).…”
Section: Introductionmentioning
confidence: 99%